Sustainability from the economic, social, environmental and mobility point of view of the Municipality of Cajica (2016)
This Essay intends to raise a sustainability problem that is going through the Municipality of Cajicá, given by an accelerated growth of the population, by the dynamics of the construction in the region. The most serious problem arises because the drinking water supply is not assured, because the municipality does not have its own sources, despite the fact that the Bogota Aqueduct and Sewerage Company provides it without a current agreement. In environmental terms, there is no infrastructure of Wastewater Treatment Plants (PTAR), there is a ruling that affects the municipalities located on the Rio Bogotá basin and it is necessary to make millionaire investments to comply. The road infrastructure is not adequate and there are problems of mobility, which make the municipality can become unattractive for investors, visitors and the local community. A large investment of infrastructure in education is required to avoid coverage problems in the short term. There are other problems, which require resources to be solved, however, municipal finances can not support the cost of investments and it becomes necessary to build regional strategies together with other municipalities with similar needs.